Impact of Popliteal Artery Entrapment Syndrome on Exercise Tolerance and Athletic Performance: A Narrative Review - Janaszek, Agnieszka; Chmurska, Agnieszka; Strzępek, Aleksandra; Smerdzyński, Mateusz; Kałwa, Natalia; Kałuża, Kinga; Frączek, Karolina; Majchrzyk, Aleksandra; Łyżwa, Julia; Pater, Michał (Journal of Education, Health and Sport, 2026)
Introduction: Popliteal artery entrapment syndrome (PAES) is a rare vascular disorder observed mainly in young, physically active individuals. It involves compression of the popliteal artery, leading to exercise-induced ischemia and reduced athletic performance. The condition is frequently underdiagnosed due to symptom overlap with musculoskeletal disorders. Methods: A narrative review was conducted based on a non-systematic search of PubMed, Scopus, and Web of Science databases, including studies published up to 2026. The analysis focused on PAES in athletic populations, covering pathophysiology, clinical presentation, diagnosis, and management. Results: PAES may be structural or functional, both resulting in impaired blood flow during exercise. Common symptoms include intermittent claudication, muscle fatigue, and paresthesia, which negatively impact exercise tolerance. Diagnosis requires dynamic imaging techniques, as resting examinations are often inconclusive. Surgical treatment provides significant improvement in most symptomatic athletes. Conclusions: PAES is an important but often overlooked cause of exercise intolerance in athletes. Early diagnosis and appropriate management are essential to restore performance and prevent long-term complications.